Mitochondrial Zea mays Brittle1-1 Is a Major Determinant of the Metabolic Fate of Incoming Sucrose and Mitochondrial Function in Developing Maize Endosperms - Bahaji, Abdellatif; Muñoz, Francisco José; Seguí-Simarro, Jose María; Camacho-Fernández, Carolina; Rivas-Sendra, Alba; Parra-Vega, Verónica; Ovecka, Miroslav; Li, Jun; Sánchez-López, Ángela María; Almagro, Goizeder; Baroja-Fernández, Edurne; Pozueta-Romero, Javier (Frontiers in Plant Science, 2019)
Zea mays Brittle1-1 (ZmBT1-1) is an essential component of the starch biosynthetic machinery in maize endosperms, enabling ADPglucose transport from cytosol to amyloplast in exchange for AMP or ADP. Although ZmBT1-1 has been long considered to be an amyloplast-specific marker, evidence has been provided that ZmBT1-1 is dually localized to plastids and mitochondria (Bahaji et al. (2011) Plant Cell Physiol. 52, 597–609). The mitochondrial localization of ZmBT1-1 suggested that this protein may have as-yet unidentified function(s). To understand the mitochondrial ZmBT1-1 function(s), we produced and characterized transgenic Zmbt1-1 plants expressing ZmBT1-1 delivered specifically to mitochondria. Metabolic and differential proteomic analyses showed down-regulation of sucrose synthase (SuSy)-mediated channelling of sucrose into starch metabolism, and up-regulation of the conversion of sucrose breakdown products generated by cell wall invertase (CWI) into ethanol and alanine, in Zmbt1-1 endosperms compared to wild-type. Electron microscopic analyses of Zmbt1-1 endosperm cells showed gross alterations in the mitochondrial ultrastructure. Notably, the protein expression pattern, metabolic profile and aberrant mitochondrial ultrastructure of Zmbt1-1 endosperms were rescued by delivering ZmBT1-1 specifically to mitochondria. Results presented here provide evidence that the reduced starch content in Zmbt1-1 endosperms is at least partly due to (i) mitochondrial dysfunction, (ii) enhanced CWI-mediated channelling of sucrose into ethanol and alanine metabolism, and (iii) reduced SuSy-mediated channelling of sucrose into starch metabolism due to the lack of mitochondrial ZmBT1-1. Our results also strongly indicate that (a) mitochondrial ZmBT1-1 is an important determinant of the metabolic fate of sucrose entering the endosperm cells, and (b) plastidic ZmBT1-1 is not the sole ADPglucose transporter in maize endosperm amyloplasts. The possible involvement of mitochondrial ZmBT1-1 in exchange between intramitochondrial AMP and cytosolic ADP is discussed.